USING INNOVATIVE MARKETING STRATEGIES IN THE DEVELOPMENT OF THE MARKET OF INFROMATION AND COMMUNICATION SERVICES - Khankeldieva Guzal Sherovna (Research Focus International Scientific Journal, 2022)
The social dimension of ICT can be recapped with the emergence of the new modes of human behavior and communication. These widespread developments in the ICT field have significantly upgraded the way people interact and communicate with each other.